Tax Justice Moderates the Effect of Tax Incentives, Online Systems, and Education Level on Individual Taxpayer Compliance - Ivira Sriwidiyanti Budi Utami; Waluyo (Universitas Pendidikan Ganesha, 2023)
Taxes are a source of state money that the government uses for the development of the community. Due to the low taxpayer compliance of individual cotributors at KPP Pratama Surabaya Gubeng, this research’s purpose is to verify the application of tax incentives, online systems, and education level on taxpayer compliance with tax justice as moderating variables. The method used is questionnaire to gather data from sample totaled 100 individual taxpayers. The statistic tool used is SmartPLS 3.0 with multiple regressions in form of PLS algorithm and bootstrapping. The outcomes show that tax incentives and education level have a positive and significant effect on individual taxpayer compliance, whereas the online system has no significant effect on individual taxpayer compliance, and tax justice does not significantly moderate tax incentives and education level on compliance. Individual taxpayers and the application of tax justice, moderates the online system's effect on individual taxpayer compliance. Tax incentive and education level found to homologise moderating variable while the online system has pure moderating impact towards individual taxpayer compliance.